Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1046/j.1360-0443.1996.91811275.x
|View full text |Cite
|
Sign up to set email alerts
|

A controlled field trial of group versus individual cognitive‐behavioural training for relapse prevention

Abstract: Results are presented of a randomized field trial comparing two aftercare regimes, namely individual versus group delivery of a structured relapse prevention approach. Two addictions treatment programs (one a 12-Step 26-day residential program, the other an evening group counselling program) implemented structured relapse prevention in either group or individual format as part of the first three months of aftercare. Process measures (e.g. attendance, client satisfaction) indicated that both group and individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 0 publications
1
24
0
3
Order By: Relevance
“…Finally, two of the identified continuing care studies did not fit into any of the above analyses (Graham, Annis, Brett, & Venesoen, 1996; Schmitz et al, 1997). Both studies compared individual to group administration of CBT continuing care.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, two of the identified continuing care studies did not fit into any of the above analyses (Graham, Annis, Brett, & Venesoen, 1996; Schmitz et al, 1997). Both studies compared individual to group administration of CBT continuing care.…”
Section: Resultsmentioning
confidence: 99%
“…Behaviour modiÿcation is integral to interventions in diverse areas such as weight reduction [1], chronic disease [2], smoking cessation [3], alcohol [4] and illicit drug [5] use, sexually transmitted disease [6] and anger management [7]. Behaviour modiÿcation programmes are often delivered to teaching subgroups of unrelated persons [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing the efficacy of group therapy to individual therapy for the treatment of SUDs have found that both treatment modalities yield similar outcomes (e.g., Graham, Annis, Brett, & Venesoen, 1996; Marques & Formigoni, 2001; Miller & Taylor, 1980; Schmitz, Bordnick, Kearney, Fuller, & Breckenridge, 1997). It is plausible that group CRAFT may provide a low-cost and feasible alternative to individual treatment while maintaining positive outcomes for concerned family members and their loved one.…”
Section: Introductionmentioning
confidence: 99%